Natural debt limit for the costa rican economy - Chaverri Morales, Carlos (2017)
The "Natural Debt Limit" (NDL) proposed by Mendoza and Oviedo (2004) is a complementary tool to the traditional indicators used to analyze debt sustainability. This limit determines the value of debt as a ratio of GDP, which is consistent with the government’s commitment to remain solvent in case the country permanently experiences a series of events that make income and expenses adjust to historical minimum levels.Using annual statistical data from the Central Government of Costa Rica for the 1985-2015 period, the NDL value for the Costa Rican economy has been estimated at 48.6%.Based on the results obtained and as part of the discussion intended with this paper, it is relevant to mention that the lack of fiscal reforms needed to increase revenue or reduce public spending would make government debt exceed the NDL value in the short term. Moreover, adjusting public spending without improving tax revenues would only delay converging the current level of debt to the defined threshold.This could limit the actions of the monetary policy to fulfill its primary objective of price stability.